2019
DOI: 10.5296/bms.v9i2.13376
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Gender Digital Divide: Overcoming the Under-Representation of South African Women in the IT Sector

Abstract: In South Africa, women are grossly underrepresented in the Information Technology (IT) sector result of gender stereotyping and discrimination. According to the Independent Communications Authority of South Africa (ICASA) Report (2017), only 21% of executives in the IT sector are women. This has caused high unemployment of women IT graduates. The purpose of this study therefore is to explore and investigate the antecedents that influence and impact the phenomenon of the gender digital divide in South Africa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The Beijing +25 Rwanda Country Report (Republic of Rwanda, 2019) notes that the "ICT literacy rate among women is still low at 7% compared to 11% of men in the same age category". The concept of the gender digital divide highlights the differences between men and women and boys' and girls' access to and use of ICT (Cooper, 2006, Nesaratnam et al, 2018. Previous studies on the use of ICT in schools and out-of-school in Rwanda (Rubagiza et al, 2011, Rubagiza, 2012) also noted a gender digital divide as well as one between rural and urban settings.…”
Section: Ii) Applicationmentioning
confidence: 99%
“…The Beijing +25 Rwanda Country Report (Republic of Rwanda, 2019) notes that the "ICT literacy rate among women is still low at 7% compared to 11% of men in the same age category". The concept of the gender digital divide highlights the differences between men and women and boys' and girls' access to and use of ICT (Cooper, 2006, Nesaratnam et al, 2018. Previous studies on the use of ICT in schools and out-of-school in Rwanda (Rubagiza et al, 2011, Rubagiza, 2012) also noted a gender digital divide as well as one between rural and urban settings.…”
Section: Ii) Applicationmentioning
confidence: 99%
“…A number of barriers may hinder female students from accessing higher education and these differ in different contexts. According to Nesaratnam et al (2022), the reasons for exclusion from higher education are difficult to unpack as they are underscored by the complex dynamics of class, gender and race. Experiences are complex and relational and are located at the intersection of structure, culture and agency (Mirza, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This technophobia translates into negative behavior towards machines that always seem difficult to operate, bad, slow or boring; or towards themselves, thinking that they are incapable of using them or that it is very difficult. In this line, Nkosingiphile et al [32] insist on the importance of training and describe that kind of coaching as a valuable element for women´s development in the Information Technology industry for various reasons, including expanding skillset and on-the-job training; specifically, they mentioned that this element acts in preventing stagnancy either in job position or job performance. It is also observed that there are few female role models in the tech world, with the exception of certain female mentors and networks.…”
mentioning
confidence: 99%